Racial Discrimination Experienced by Black People as Reflected in Langston Hughes's Poems - Mutmainnah; Arafah, Burhanuddin; Pattu, Amir (Journal of language teaching and research, 2022)
This study aims to describe the racial discrimination from white people against black people that was formerly a slave by analyzing Langston Hughes' poems; I, Too, To the Black Beloved, The White Ones, and My Beloved. Presentation of racial discrimination can be seen from the act of prejudice, insulting, words used, and the act of suppression to the black people. These poems represent the poet's feeling of social phenomena that happened. The data were analyzed utilizing the new historicism theory, enriched by historical text, socio-cultural, and political information during slavery. This study is a qualitative descriptive method using the new historicism approach to explain the racial discrimination experienced in Langston Hughes' poems. The result showed that Langston Hughes reflects the phenomena of racial discrimination through his poems, such as slave, victim, nigger, torture, darker brother, and not beautiful in his poems. Langston Hughes in his poetry concludes that black discrimination is treated badly; they eat in the kitchen, they are not beautiful, children's happiness is tarnished, and racial discrimination is inhumane.